Peer review of the pesticide risk assessment of the active substance Cydia pomonella granulovirus (CpGV). (7th November 2022) - ,; Alvarez, Fernando; Arena, Maria; Auteri, Domenica; Binaglia, Marco; Castoldi, Anna Federica; Chiusolo, Arianna; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; De Lentdecker, Chloe; Egsmose, Mark; et al.
Abstract: The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State Germany and co‐rapporteur Member State the Netherlands for the pesticide active substance Cydia pomonella granulovirus (CpGV) and the considerations as regards the inclusion of the substance in Annex IV of Regulation (EC) No 396/2005 are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative uses of CpGV as an insecticide on pome fruit (apple, pear, quince, nashi pears, medlars), stone fruit (peach, apricot, nectarine, almond, plum trees), walnut trees (field foliar spray applications, professional and non‐professional uses). The reliable end points, appropriate for use in regulatory risk assessment are presented. Missing information identified as being required by the regulatory framework is listed.